Characteristics of tuna fisheries in the Indian Ocean, especially in Quota Based Fishing in the Zone 04 (IFMA 572 and 573) - Mahrus, Mahrus; Nurani, Tri Wiji; Wisudo, Sugeng Hari; Iskandar, Budhi Hascaryo; Suherman, Agus; Noegroho, Tegoeh (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Indonesia is one of the worlds leading tuna-producing countries. Under the Quota Based Fishing (Penangkapan Ikan Terukur/PIT), its Exclusive Economic Zone (ZEEI) in the Indian Ocean is designated as zone 04 of PIT. This research aims to analyzing the characteristics of tuna fisheries in the zone 04 (Indonesian Fisheries Management Area/IFMA 572 and 573), including tuna production by fishing gear and by port landing, species composition by gear, Landing per Unit Efforts (LPUE) by gear and by tuna species. The most dominant fishing gear for tuna is lines (hand lines, troll lines, kite lines, and rod handlines). Purse seines and longlines also caught a lot of tuna, but their percentages were still lower. The dominant tuna species caught was yellowfin tuna, which came from all types of fishing gear. The average LPUE in 2024 for gillnets was 28.6 kg/days, lines 56 kg/days, purse seine 161 kg/days, longline 58.5 kg/days, and pole and line 268 kg/trip/day. The abundance of ALB was highest in July, but the trend has been increasing since March and began to decline in last year. Pole and line and purse seine were the most productive fishing gear for catching tuna. The abundance of YFT varied greatly with high abundance in March, July, and October. The abundance of BET was high in February, July, and September. SBT is highly abundant in March, April, and July, with some months being empty. Benoa Public Port is recorded as the port with the highest production within Zone 04.Keywords:Tuna fisheriesIndian OceanTuna ProductionComposition speciesLPUEFishing Quotas